Askese, Misi Transformasi Diri: Dialog Iman Katolik dengan Serat Wedhatama - Kurniawan, Heru (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2015)
The article explores the inherent relation between faith and culture in human life, individually as well as communally. The writer particularly analyses the Christian faith in the Javanese context, where he finds out that there is a close connection between the ascetic-mystical practice in Christianity and the one of the Javanese tradition, namely Serat Wedhatama. Serat Wedhatama (‘ajaran utama’, ‘prime instruction’ or ‘primary teaching’, which means ‘exalted wisdom’) was composed by Kanjeng Gusti Pangeran Adipati Arya Mangkunegara IV (KGPAA Mangkunegara IV,1809–1881), a prominent poet of Surakarta Principality, Central Java. Wedhatama praises morality (wirya, arta, winasis – dignity, wealth, knowledge) which is consistent to the mystical Javanese Islam, in contrast to the more self-consciously Orthodox Islamic community. With regard to religion (agama: ageming aji), with its four levels of sembah raga, sembah cipta, sembah suksma, sembah rasa (worshipping God with one’s body, mind, and soul to be in unity with the Almighty), Wedhatama seems to be correspondent with the long ascetic-mystical Christian tradition. The writer argues that the encounter of the two traditions is precisely the excellent way of being a true Javanese Christian as well as witnessing to the society at large.